If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -1 + -1y = 0 Reorder the terms: -1 + 3y + -1y = 0 Combine like terms: 3y + -1y = 2y -1 + 2y = 0 Solving -1 + 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2y = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2y = 0 + 1 2y = 0 + 1 Combine like terms: 0 + 1 = 1 2y = 1 Divide each side by '2'. y = 0.5 Simplifying y = 0.5
| 15d-20=35 | | 10(5x-3)=120 | | 2(3x-5)=90 | | 5n-35=5(1-7n) | | 8.75+40x=13.25x+509.00 | | x(1.5x+3)=120 | | 8x+12x=268 | | 7-5m=-8 | | X+13=2x-5 | | 2(2x+40)+2(5x)=360 | | 2x+0=x+1 | | 5-3x+1=5x-2 | | 2(0)+y=0+1 | | -4x-39=59-9x | | p=r+p | | 25m+75=30m | | x+29y=180 | | 5x+28=40-7x | | 25-x=18.6 | | 5x+3x-8=2x+16 | | 130d=2r | | 2x+(x+2)=4 | | 22-y=1 | | 30c=75 | | 29y+x=180 | | 5a+4(3a-8)=x-8x | | 10-x=-23 | | -27-11+16+67+15-31= | | -2c-10+5c-25= | | 3(-2+3x)=9x-4 | | t-2c=5 | | 5-x-2=3+4x+5x |